New insights into the genetic diversity of the stone crayfish: taxonomic and conservation implications - Lovrenčić, Leona; Bonassin, Lena; Boštjančić, Ljudevit Luka; Podnar, Martina; Jelić, Mišel; Klobučar, Göran; Jaklič, Martina; Slavevska-Stamenković, Valentina; Hinić, Jelena; Maguire, Ivana (Springer Science and Business Media LLC, 2020)
Austropotamobius torrentium is a freshwater crayfish species native to central and south-eastern Europe, with an intricate evolutionary history and the highest genetic diversity recorded in the northern-central Dinarides (NCD). Its populations are facing declines, both in number and size across its entire range. By extanding current knowledge on the genetic diversity of this species, we aim to assist conservation programmes. Multigene phylogenetic analyses were performed using different divergence time estimates based on mitochondrial and, for the first time, nuclear DNA markers on the largest data set analysed so far. In order to reassess taxonomic relationships within this species we applied several species delimitation methods and studied the meristic characters with the intention of finding features that would clearly separate stone crayfish belonging to different phylogroups.
Keywords: Austropotamobius torrentium, Species delimitation, Species validation, MOTU, ESU, Phylogeographic patterns, nuDNA, mtDNA, Evolutionary history